Ritual stone‐built architecture and shell midden foundation: A semisubterranean structure in hyperarid Atacama Desert coast, Northern Chile. Issue 1 (7th May 2021) - Power, Ximena; Sitzia, Luca; Yrarrázaval, Sebastián; Salazar, Diego; Andrade, Pedro; Hernández, Valentina; Aliste, Catalina; Muth, Xavier
Abstract: Hunter‐gatherer architectural practices are one of the main sources of data to understand the complex land use of these societies. In the hyperarid Atacama Desert coast (Northern Chile), hunter‐gatherers‐fishers developed standardized stone‐built architecture during the Late Archaic period (∼5, 700–4, 000 cal years BP), interpreted so far as sedentary villages or long‐term campsites. Nevertheless, the lack of site formation process studies and systematic chronostratigraphies defy such functional interpretations. To address these issues, we reconstruct the lifecycle of a recently discovered semisubterranean structure at the Zapatero site (~25°S, Taltal). Combining stratigraphy, micromorphology, faunal and lithic analysis, as well as radiocarbon dating, we evidence a broad sequence involving different processes: shell midden formation; a stone‐structure; a prepared burial pit; a burning event; a short‐term occupational episode; and the entombment of the structure. We interpret this sequence as ritualized actions related to commemorative and place‐making activities. Our work stresses the need for new research programs at the Atacama Desert coast, based on geoarchaeological approaches, to understand hunter‐gatherer‐fisher middening and architectural practices from the very materiality involved in stratigraphy‐making processes. Abstract : Top left: Middle Holocene stone‐built architectonic feature (Structure‐2) and local geomorphological context of Zapatero site. Bottom left: Stratigraphic sequence of Structure‐2. Top right: Micromorphological blocks sampled in the stratigraphic sequence and main microfacies identified. Lower right: Examples of multiple‐item nodules (MINs) and lithic artifacts from the studied stratigraphic units.